E-Laboratory in Education System - et. al., K.Geetha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Internet technology has provided further teaching and learning ways in today’s world. At present, most institutes prefer the concept of Learning Management System/E-Learning for improving their learning system. The proposed system E-laboratory has various programming languages that can be accessed through the internet, remotely by the student, distance learners, and staff members. During this pandemic COVID-19 situation, the E laboratory (E-LAB) plays a vital role in the education system for gaining hands-on experience in accessing various tools and applications remotely. It is very much helpful in these situations for everyone to work and learn in a self-paced manner.